Analisis Keterampilan Dasar Pemimpin Kelompok pada Mahasiswa yang Mengikuti Praktikum Prosedur Kelompok dalam Konseling - Ade Chita Putri Harahap (Program Studi Bimbingan Penyuluhan Islam Fakultas Dakwah dan Komunikasi, 2021)
The group creates a formation process within the group itself by bringing up the dynamics in it so that certain goals are achieved. Groups are formed by BK/Counselors who play an important role in BKp and KKp services. Leaders are closely related to group activities. Group leaders have a strong influence in the group service process, not only must direct the behavior of group members according to needs, but must be responsive to all changes that occur in the group as a result of the development of group activities. Therefore, to be able to carry out their duties, roles and functions as group leaders, the personality and skills of the counselor are central in the therapeutic process, so all theoretical models devote a lot of attention to group leaders. This study aims to determine the basic skills of group leaders in conducting practical group procedures in counseling. The number of samples in this study were 112 students of BKI study program. Based on the results of the study, it was found that most of the students had basic group leader skills with a high category of 37.5%, most of the others were in the medium category that was 28.5%, the low category was 25% and the very low category was 9 %. Overall, the basic skill level of group leaders in BKI students is in the medium category (112.58%).